Author Correction: Vertical migration by bulk phytoplankton sustains biodiversity and nutrient input to the surface ocean - Kai Wirtz; S. Lan Smith (Scientific Reports, 2021)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.